The myo-inositol/proton symporter IolT1 contributes to d-xylose uptake in Corynebacterium glutamicum. (February 2018) - Brüsseler, Christian; Radek, Andreas; Tenhaef, Niklas; Krumbach, Karin; Noack, Stephan; Marienhagen, Jan
Highlights: Deletion of iolR improves growth of C. glutamicum on d -xylose containing media. Permease IolT1 contributes to d -xylose uptake in C. glutamicum. Engineering of the iolT1 promoter renders iolR -deletion unnecessary. Minimally engineered C. glutamicum WMB2 PO6 iolT1 allows for high growth rates on d -xylose. Abstract: Corynebacterium glutamicum has been engineered to utilize d -xylose as sole carbon and energy source. Recently, a C. glutamicum strain has been optimized for growth on defined medium containing d -xylose by laboratory evolution, but the mutation(s) attributing to the improved-growth phenotype could not be reliably identified. This study shows that loss of the transcriptional repressor IolR is responsible for the increased growth performance on defined d -xylose medium in one of the isolated mutants. Underlying reason is derepression of the gene for the glucose/ myo -inositol permease IolT1 in the absence of IolR, which could be shown to also contribute to d -xylose uptake in C. glutamicum . IolR-regulation of iolT1 could be successfully repealed by rational engineering of an IolR-binding site in the iolT1 -promoter. This minimally engineered C. glutamicum strain bearing only two nucleotide substitutions mimics the IolR loss-of-function phenotype and allows for a high growth rate on d -xylose-containing media (µmax = 0.24 ± 0.01 h −1 ).